Interactions between Typhoon Choi-wan (2009) and the Kuroshio Extension System - Akiyoshi Wada; Norihisa Usui; Masaru Kunii (Advances in Meteorology)
We investigated interactions between Typhoon Choi-wan (2009) and the Kuroshio Extension system with a coupled atmosphere-wave-ocean model in 14 numerical simulations performed with initial conditions obtained from daily oceanic reanalysis data for the northwestern Pacific Ocean from September 12 to September 25, 2009. Preexisting oceanic conditions affected the simulated central pressure and the inner-core axisymmetric structure of the simulated typhoon differently during the intensification, mature, and decaying phases, but they had little impact on the simulated track. Among the simulations, the simulated central pressure range during the mature phase was ~10 hPa. Simulated central pressure was highly correlated with the axisymmetric mean horizontal specific humidity flux between radii of 50 and 150 km and altitudes of 20 to ~2000 m, suggesting that this flux has potential as a new metric for predicting tropical cyclone intensity. Variations in preexisting oceanic conditions in the Kuroshio Extension region on the simulated atmospheric and oceanic horizontal fields affected the typhoon and a nearby stationary front differently. Around the stationary front, the impact on hourly precipitation was closely related to that on surface wind speed, whereas the impact on surface temperature was greatly affected by that on sea surface temperature through the latent heat flux.